The Increase of Periodontal Tissue in Type 2 Diabetes Mellitus Patients Based on Index CPITN - Budiman, Budiman (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
The prevalence of periodontal disease in Indonesia for all age groups has reached 96.58%. Periodontal disease has been identified as a consequence of diabetes mellitus (DM). The purpose of this study is to determine the differences of periodontal tissues in type 2 diabetes and non-diabetic patients based on CPITN index (Community periodontal index of Treatment index). This study employed case control design. The population of the study consisted of 3.544 visits in the Internal Disease Polyclinic of RSUD Cimahi Cibabat in January 2015. The samples for case group were 50 people (diabetes mellitus type 2) and control group were 50 people (non-DM). The sampling technique used accidental sampling. The study was conducted in 2015 by conducting measurement of periodontal pocket depth using CPITN index. The analysis of data was carried out with independent T test. The results show that the average pocket depth based on CPITN index in the case group of type 2 DM (4.26) is greater than control group of patients without DM (3.14). There is different condition on the periodontal tissue in the group of type 2 diabetes (value-p = 0.002 <0.05). The awareness in increasing the oral health protection is done by providing consultation related to blood glucose.